Impact of doping and spin-polarization on the γ-Fe/Cr2O3 interfacial adhesion - Mingtai Zou; Wen Tong Geng; Wei Xu; Chenchong Wang (Journal of Materials Research and Technology, 2025)
In natural service environments, the surface of traditional stainless steel, heterogeneous alloys or gradient materials with γ-Fe matrix is vulnerable to the external environment and the combined effects of mechanical stress, leading to easy detachment of the metal and oxide film. Strengthening the bonding of the γ-Fe passivation film is crucial for enhancing the corrosion resistance of the material. This study utilized first-principles calculations to systematically explore the γ-Fe/Cr2O3 interface, with a particular emphasis on the impact of spin-polarization and the synergistic interactions between alloy elements and the interface. The computational findings reveal that incorporating magnetic settings in the Fe/Cr2O3 system significantly enhances calculation accuracy and confirms the existence of an Fe2O3 transition layer at the interface. Meanwhile, incorporating spin polarization alters the effect of Al on interfacial binding energy. Furthermore, this study clarifies the intricate interactions between the passivation film and the synergistic effects of two alloy elements.